The Correspondence of Wolfgang Capito : Volume 2: 1524-1531 - Capito, Wolfgang, 1478-1541 (Book collections on Project MUSE., 2005)
A fully annotated translation of the correspondence of Protestant leader Wolfgang Capito (1478-1541) for the years 1532-36, this volume provides crucial details on the evolution of Capito's thought and its contribution to the Reformation movement. This title was made Open Access by libraries from around the world through Knowledge Unlatched. Wolfgang Capito (1478-1541), a leading Christian Hebraist and Catholic churchman who converted to Protestantism, was a pivotal figure in the history of the Reformation. After serving as a professor of theology in Basel and adviser to the archbishop of Mainz, he moved to Strasbourg, which became, largely due to his efforts, one of the most important centres of the Reformation movement after Wittenberg. This penultimate volume in the series is a fully annotated translation of Capito's existing correspondence covering the years 1532-36 and culminating in the Wittenberg Concord between the Lutheran and Reformed churches. The correspondence includes Capito's efforts, alongside those of his colleague Martin Bucer, to negotiate that compromise. Other letters deal with local, political, financial, and doctrinal questions, as well as Capito's personal life. The letters demonstrate the importance of Capito and his colleagues in providing advice in matters concerning the churches in southern Germany and Switzerland, but also regarding the evangelicals in neighbouring France. Milton Kooistra's annotation provides historical context by identifying classical, patristic, and biblical quotations as well as persons and places. Continuing in the series' tradition of rigorous scholarship, this volume provides crucial details on the evolution of Capito's thought and its contribution to the Reformation movement.